1996
DOI: 10.1007/s002040050252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzene metabolite treatment on granulocytic differentiation and DNA adduct formation in HL-60 cells

Abstract: Reactive metabolites of benzene (BZ) play important roles in BZ-induced hematotoxicity. Although reactive metabolites of BZ covalently bind to DNA, the significance of DNA adduct formation in the mechanism of BZ toxicity is not clear. These studies investigated the covalent binding of the BZ metabolites hydroquinone(HQ) and 1,2,4-benzenetriol(BT) using the DNA [32P]postlabeling method and explored the potential relationship between DNA adduct formation and cell differentiation in human promyelocytic leukemia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…We recently evaluated the significance of DNA adduct formation in toxicity by studying the effects of benzene metabolites on DNA adduct formation and retinoic acid-induced granulocytic differentiation in this model (38). Table 3 shows that while treatment of HL-60 cells with 50 ,uM hydroquinone for 1 to 4 hr induced the formation of a single DNA adduct that increased with increasing time of exposure, no adducts were detected in cells treated with 50 to 500 pM 1,2,4-benzenetriol for up to 4 hr.…”
Section: Microsomal Metabolismmentioning
confidence: 99%
“…We recently evaluated the significance of DNA adduct formation in toxicity by studying the effects of benzene metabolites on DNA adduct formation and retinoic acid-induced granulocytic differentiation in this model (38). Table 3 shows that while treatment of HL-60 cells with 50 ,uM hydroquinone for 1 to 4 hr induced the formation of a single DNA adduct that increased with increasing time of exposure, no adducts were detected in cells treated with 50 to 500 pM 1,2,4-benzenetriol for up to 4 hr.…”
Section: Microsomal Metabolismmentioning
confidence: 99%
“…The observed increase in white blood cells and platelets count could be attributed to acute response of the myeloid and megakaryotic stem cells to high dosage of the oil. Studies have shown that these stem cells have the selective advantage of proliferation and resistance to acute toxicity of crude oil and its metabolites 16,[32][33] .…”
Section: Resultsmentioning
confidence: 99%
“…The metabolites of benzene and polycyclic aromatic hydrocarbon have been shown to be very potent carcinogens [16][17][18] . The present study, investigates the effect of Bonny light crude oil on some hematological parameters in guinea pigs.…”
Section: Introductionmentioning
confidence: 99%
“…DNA damage, formation of DNA adducts, chromosomal aberrations such as aneuploidy, increased formation of micronuclei and sister chromatid exchanges) of benzene and its metabolites (namely HQ, 1,4-BQ, 1,2,4-BT and catechol) is the most reported key event observed in the identified in vitro studies Bodell et al, 1996;Chung et al, 2002;Hedli et al, 1996;Ishihama et al, 2008;Levay & Bodell, 1992;Levay et al, 1993;Lindsey et al, 2005;Lindsey et al, 2004;Mondrala & Eastmond, 2010;Oikawa et al, 2001;Pandey et al, 2009;Pasquini et al, 2003;Thys et al, 2015;Winn, 2003;Zhang et al, 1993;Zhang et al, 1994;Zhang et al, 1998). Then it is followed by oxidative stress as an early key event associated with benzene and its metabolites (Badham & Winn, 2010a;Goldman et al, 1999;Ishihama et al, 2008;Kolachana et al, 1993;Li & Trush, 1993;Nishikawa et al, 2012;Oikawa et al, 2001;Ruiz-Ramos et al, 2005;Wan & Winn, 2007;Wiemels & Smith, 1999;Zhang et al, 1993).…”
Section: Supporting Publications 2016: En-955 129mentioning
confidence: 99%